Synthesis and Application of Covalently Grafted Magnetic Graphene Oxide Carboxymethyl Cellulose Nanocomposite for the Removal of Atrazine From an Aqueous Phase. Issue 12 (2nd December 2021) - Khawaja, Heena; Zahir, Erum; Asghar, Muhammad Asif; Rafique, Kashif; Asghar, Muhammad Arif
Abstract: The nanocomposite of magnetic graphene oxide cross-linked with carboxymethyl cellulose (GO-CMC-Fe) was synthesized using a facile, economical, and environment friendly approach. The highly stable sponge-like porous structure and chemical functionalities of the GO-CMC-Fe nanocomposite were demonstrated using UV-visible spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive X-Ray (EDX), and Fourier transform infrared spectroscopy (FTIR) analysis. The adsorption properties of the GO-CMC-Fe together with GO, GO-CMC, and GO-Fe in terms of atrazine removal were examined in batch mode as a function of various removal parameters. The equilibrium statistics of the adsorption process were defined by the Langmuir isotherm model with maximum removal capacities of 126, 142, 158, and 194 mg/g for GO, GO-Fe, GO-CMC, and GO-CMC-Fe, respectively. The rapid adsorption process followed a pseudo-second-order kinetic model due to greater R 2 values (>0.997) than the pseudo-first-order kinetic model and considered the chemisorption adsorption process and rate limiting step. On the other hand, spontaneity, endothermic nature, and increased randomness during the adsorption process were confirmed by the negative values of Gibbs free energy and positive values of enthalpy and entropy, respectively. The cost for the immobilization of atrazine from aqueous solution would range between $20–$50 per million liters, which is much more cost-effective than earlier reported techniques. In conclusion, the GO-CMC-Fe nanocomposite showed great potential to remove atrazine from aqueous solution to manage wastewater pollution.